Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 1 - Some Basic Concepts of Arithmetic and Algebra - 1.3 - Integers: Addition and Subtraction - Problem Set 1.3 - Page 20: 95



Work Step by Step

RECALL: $-(-a)=a$ AND $a-b=a+(-b)$ Substitute the given values of the variables to obtain: $-x-y-z = -(-2)-3-(-11)$ Use the rule above to obtain: $=2-3-(-11) \\=(2-3)-(-11)$ Apply the second rule above to the expression inside the parentheses to obtain: $=[2+(-3)]-(-11) \\=(-1) - (-11)$ Apply the rule above to obtain: $=-1+11 \\=10$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.